CD109: a multifunctional GPI‐anchored protein with key roles in tumor progression and physiological homeostasis. Issue 5 (20th June 2019) - Mii, Shinji; Enomoto, Atsushi; Shiraki, Yukihiro; Taki, Tetsuro; Murakumo, Yoshiki; Takahashi, Masahide
Abstract : CD109 is a glycosylphosphatidylinositol‐anchored glycoprotein and a member of the α2 ‐macroglobulin/C3, C4, C5 family of thioester‐containing proteins first identified as being expressed on blood cells, including activated T cells and platelets, and a subset of CD34 + bone marrow cells containing megakaryocyte progenitors. Although CD109 carries the biallelic platelet‐specific alloantigen Gov, the physiological functions or roles of CD109 in human disease remain largely unknown. It was recently demonstrated that CD109 is expressed in many malignant tumors, including various squamous cell carcinomas and adenocarcinomas, and plays a role as a multifunctional coreceptor. CD109 reportedly associates with transforming growth factor (TGF)‐β receptors and negatively regulates TGF‐β signaling in keratinocytes. Additionally, CD109 is potentially related to signal transducer and activator of transcription‐3 signaling and aberrant cell proliferation. In this review, we describe recent evidence of CD109‐specific significance in malignant tumors shown in mouse models and human tissues. Furthermore, we discuss the physiological functions of CD109 in vitro and in vivo, including results of phenotype analyses of CD109‐deficient mice exhibiting epidermal hyperplasia and osteopenia.